(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The objective of this work is to develop a proposal for digitalization of the financial debt claim process of a health services organization in the city of Mar del Plata, Argentina. Given the growth in the number of clients, delays have been generated in the process and shortcomings in integration, communication and coordination between the areas involved. This situation generates the main problem that the organization faces financial problems associated with lack of liquidity, with the impossibility of meeting all of the obligations and commitments assumed. For this reason, the digitalization of all the information and documentation associated with the process and the implementation of the agile Kanban methodology is proposed to be able to manage it quickly, flexibly and integratedly. A virtual dashboard is designed to visualize the process flow, policies, work-in-progress limits, feedback cycles and continuous improvement are established. It is concluded that the proposal for digitalization and agile management of the analyzed process will generate a positive impact on the organization’s finances, both in the short and long term, favoring its solvency, future competitiveness and continuously adding value to the organization